2018
DOI: 10.3389/fphar.2018.01377
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Quality Control Method for Saponins Without UV Absorption by UPLC-QDA

Abstract: Saponins are a class of important active ingredients. Analysis of saponin-containing herbal medicines is a major challenge for the quality control of medicinal herbs in companies. Taking the medicine Astragali radix (AR) as an example, it has been shown that the existing evaporative light scattering detection (ELSD) methods of astragaloside IV (AG IV) has the disadvantages of time-consuming sample preparation and low sensitivity. The universality of ELSD results in an inapplicable fingerprint with huge signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The sample preparation for the AG IV determination in the Chinese Pharmacopoeia (National Commission of Chinese Pharmacopoeia, 2015) (version 2015) involves reflux extraction, liquid-liquid separation with n-butanol, and liquidliquid separation with ammonia, which may take more than 2 days to complete per sample. Therefore, we optimized and established practical method for the determination of AG IV content in raw materials and pieces of AR (Zhao et al, 2018). This method replaces all of the time-consuming preparation steps with sonication extraction and ammonia hydrolysis, shortening the preparation time from around 2 days to less than 2 h. Sample preparation methods and analysis methods were optimized in this study for freeze-dried powder and formula granules of AR as described below.…”
Section: Methods Optimization For the Analysis Of Astragaloside IVmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample preparation for the AG IV determination in the Chinese Pharmacopoeia (National Commission of Chinese Pharmacopoeia, 2015) (version 2015) involves reflux extraction, liquid-liquid separation with n-butanol, and liquidliquid separation with ammonia, which may take more than 2 days to complete per sample. Therefore, we optimized and established practical method for the determination of AG IV content in raw materials and pieces of AR (Zhao et al, 2018). This method replaces all of the time-consuming preparation steps with sonication extraction and ammonia hydrolysis, shortening the preparation time from around 2 days to less than 2 h. Sample preparation methods and analysis methods were optimized in this study for freeze-dried powder and formula granules of AR as described below.…”
Section: Methods Optimization For the Analysis Of Astragaloside IVmentioning
confidence: 99%
“…Extraction and preparation of AR pieces was carried out as described in our previous study (Zhao et al, 2018). Each sample of freeze-dried powder and formula granules was accurately weighed, 0.3 and 0.5 g, respectively, placed in a 50 ml centrifuge tube.…”
Section: Sample Preparation For Astragaloside IV Content Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies on astragaloside IV (AS-IV) are more and more increasingly popular. A simple and fast quantification method for AS-IV has been established with ultra-performance liquid chromatography (UPLC-QDA) [47]. In addition, it has been confirmed that AS-IV is the main bioactive constituent among the Astragalus saponins, which has been reported to exert extensive pharmacological actions in various diseases [36].…”
Section: Chemical Compositionmentioning
confidence: 99%